Validation of the Alternative International Prognostic Score‐E (AIPS‐E): Analysis of Binet stage A chronic lymphocytic leukemia patients enrolled into the O‐CLL1‐GISL protocol. (7th April 2021) - Morabito, Fortunato; Tripepi, Giovanni; Vigna, Ernesto; Bossio, Sabrina; D'Arrigo, Graziella; Martino, Enrica Antonia; Storino, Francesca; Recchia, Anna Grazia; Fronza, Gilberto; Di Raimondo, Francesco; Colombo, Monica; Fais, Franco; et al.
Abstract: Objectives: To validate the predictive value on time to first treatment (TTFT) of AIPS‐E and IPS‐E evaluated in an independent cohort of newly diagnosed and non‐referred Binet stage A CLL patients enrolled in the O‐CLL1‐GISL protocol (clinicaltrial.gov identifier: NCT00917540). Methods: A cohort of 292 newly diagnosed Binet A CLL cases has been enrolled in the study. Patients from several Italian Institutions were prospectively enrolled within 12 months of diagnosis into the O‐CLL1‐GISL protocol. Results: The majority of patients were male (62%); median age was 60.4 years, 102 cases (34.9%) showed unmutated IGHV genes, 8 cases (2.8) the presence of del(11q)/del(17p), 142 cases (48.6%) the presence of palpable lymph nodes and 146 cases (50%) and ALC > 15 × 10 9 /l. After a median follow‐up of 7.2 years, 130 patients underwent treatment. According to the AIPS‐E, 96 patients were classified as low‐risk, 128 as intermediate‐risk, and 68 as high‐risk. These groups showed significant differences in terms of TTFT. The C‐statistic was 0.71 ( P  < .0001) for predicting TTFT. According to IPS‐E, 77 patients were classified as low‐risk, 135 as intermediate‐risk, and 80 as high‐risk. These groups showed significant differences in terms of TTFT. The C‐statistic was 0.705 ( P  < .0001) for predicting TTFT. Conclusions: Our data confirm an accurate prognostic utility of both AIPS‐E and IPS‐E at the individual patient level. These data may be useful for a precise stratification of early‐stage patients.